The Role of the Danish Language in Iceland - Hauksdóttir, Auður (Linguistik Online, 2016)
Due to the long-standing relationship between Denmark and Iceland, the Danish language has played a significant role in Iceland for a long time. With urbanisation in the 19th century, a relatively high number of Danes settled in Reykjavík and Danish language and culture which was highly different from the traditional Icelandic rural culture became predominant in the city. With a growing national consciousness, the use of Danish and Danish loanwords came to be regarded as a threat to the mother tongue. However, greater independence gradually led to more balanced attitudes. Knowledge of Danish was a key to education, as many Icelanders sought education of different types in Denmark. Danish was taught as a foreign language in Icelandic schools. Icelandic was the language of instruction in all subjects, although some of the textbooks were in Danish. The relationship with Denmark and the other Scandinavian countries remains close. Danish is still a compulsory subject in Icelandic primary and grammar schools and, nowadays, provides Icelanders with a key to understanding and using the rest of the Scandinavian languages.